The Effect of Cash Management and Credit Policy on Liquidity and Profitability of MSMEs in Bandung City - Hidayat, Gustina; Kartiwa, AA; Putro, Herman Purwoko (West Science Interdisciplinary Studies, 2024)
This study examines the impact of Cash Management and Credit Policy on the Liquidity and Profitability of Micro, Small, and Medium Enterprises (MSMEs) in Bandung City. Utilizing a quantitative research approach, data were collected from 210 MSMEs through structured questionnaires employing a Likert scale ranging from 1 to 5. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results reveal that both Cash Management and Credit Policy have significant positive effects on the Liquidity and Profitability of MSMEs. Specifically, effective Cash Management enhances a firm’s ability to meet short-term obligations, thereby improving Liquidity, while robust Credit Policy practices directly contribute to both Liquidity and Profitability by ensuring timely collections and minimizing the risk of bad debts. These findings underscore the critical role of strategic financial management in sustaining the financial health and growth of MSMEs in Bandung City.